Array - Ushoifiroh, Zida Gusti (The Commercium, 2022)
This study aims to identify and describe the promotion strategy, which is carried out by local online transportation service Cak Ed Delivery Lamongan, to increase the number of customers. By using case study methods and qualitative research types. Researchers conducted observations and interviews based on data obtained from primary data sources, namely the owner of Cak Ed Delivery, Cak Ed Delivery workers, and collaborating partners. Then analyze the data findings with marketing mix theory. The results of this study indicate that the marketing communication strategy is the main basis for local start-up Cak Ed Delivery through promotional activities on social media, giving free vouchers, holding giveaways and collaborating with various partners. As a local start-up, Cak Ed Delivery strives to develop business and compete with competitors in the same field in Lamongan, by providing solutions to address the needs of the Lamongan community, through the services offered and adapting to Lamongan environmental conditions.